2018
DOI: 10.1029/2018jd028527
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Seasonal Variation in Primary and Secondary Organic Aerosols in Beijing, China

Abstract: Biomass burning (BB) aerosols, primary biological aerosol particles, and secondary organic aerosols, are critical components of particulate matter in the atmosphere. In this study, saccharides, lignin/resin acids, biogenic secondary organic aerosols tracers, aromatic acids, and hydroxyacids/polyacids were measured in total suspended particles collected from April 2012 to March 2013 at an urban site in Beijing using gas chromatography/mass spectrometry. The concentration of levoglucosan was elevated during 18-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 131 publications
5
39
1
Order By: Relevance
“…lease microorganisms along with plant debris into the atmosphere, strong air motions induce higher dispersion. These observations are in good agreement with those previously reported (Jones and Harrison, 2004;Liang et al, 2013;Zhang et al, 2010Zhang et al, , 2015Zhu et al, 2018b). For instance Liang et al (2013) have found a negative correlation between wind speed and polyol concentrations, and the highest atmospheric fungal spores concentrations were observed for a wind speed range of 0.6 to 1.0 m s −1 .…”
Section: Influence Of Meteorological Parameters On Ambient Concentratsupporting
confidence: 93%
See 2 more Smart Citations
“…lease microorganisms along with plant debris into the atmosphere, strong air motions induce higher dispersion. These observations are in good agreement with those previously reported (Jones and Harrison, 2004;Liang et al, 2013;Zhang et al, 2010Zhang et al, , 2015Zhu et al, 2018b). For instance Liang et al (2013) have found a negative correlation between wind speed and polyol concentrations, and the highest atmospheric fungal spores concentrations were observed for a wind speed range of 0.6 to 1.0 m s −1 .…”
Section: Influence Of Meteorological Parameters On Ambient Concentratsupporting
confidence: 93%
“…These results highlight that ambient air temperature and humidity are key meteorological drivers of the annual variation cycles of polyol and glucose concentrations. Hot and dry ambient air conditions may decrease the metabolic activity of the microorganisms (e.g., microbial growth and sporulation) (Fang et al, 2018;Liang et al, 2013;Meisner et al, 2018). Finally, maximum ambient concentration levels for both SC and cellulose are observed in excellent temporal agreement with the harvest periods (late summer) at the OPE-ANDRA site (Fig.…”
Section: Specific Case Of a Highly Impacted Agricultural Areamentioning
confidence: 65%
See 1 more Smart Citation
“…These observations are in good agreement with those previously reported (Jones and Harrison, 2004;Liang et al, 2013;Zhang et al, 2010Zhang et al, , 2015Zhu et al, 2018b). For instance Liang et al (2013) have found a negative correlation between wind speed and polyol concentrations, and the highest atmospheric fungal spores concentrations were observed for a wind speed range of 0.6 to 1.0 m s −1 . One of the limitations of this study is that 4 d averaged observations do not allow us to evaluate the driver contributions that might explain some short-term events for which the influence of meteorological parameters such as rainfall or solar radiation could also be significant (Grinn-Gofroń et al, 2019;Heald and Spracklen, 2009;Jones and Harrison, 2004).…”
Section: Influence Of Meteorological Parameters On Ambient Concentratsupporting
confidence: 93%
“…These results highlight that ambient air temperature and humidity are key meteorological drivers of the annual variation cycles of polyol and glucose concentrations. Hot and dry ambient air conditions may decrease the metabolic activity of the microorganisms (e.g., microbial growth and sporulation) (Fang et al, 2018;Liang et al, 2013;Meisner et al, 2018 Finally, maximum ambient concentration levels for both SC and cellulose are observed in excellent temporal agreement with the harvest periods (late summer) at the OPE-ANDRA site (Fig. 6).…”
Section: Specific Case Of a Highly Impacted Agricultural Areamentioning
confidence: 71%